Perlindungan Hak atas Lingkungan Sehat dalam Tindak Pidana Penebangan Hutan Tanpa Izin: Perspektif Hak Asasi Manusia - Septiani, Annisa Eka; Salsabella, Aulia Rizky Rahma Najwa; Aryana, Riska; Azzahra, Annisa Adelita; Vina, Kina Okta (Universitas Sang Bumi Ruwa Jurai, 2025)
This study aims to analyze the protection of the right to a healthy environment in cases of illegal logging from a human rights perspective. From an axiological perspective, this study emphasizes that law does not merely function as a written norm, but has instrumental value in realizing ecological justice, sustainable development, and protecting the rights of present and future generations. This value requires the state, authorities, and society to work together to preserve the environment as an integral part of human rights. The research method used is normative juridical with a legislative approach, human rights doctrine, and case studies of illegal logging. The results show that illegal logging causes ecological damage, loss of resources, and serious violations of the basic rights of communities, especially vulnerable groups who depend on forests. Existing legal protection is still formalistic and weak in implementation, especially in the aspects of law enforcement and environmental restoration. Therefore, strengthening human rights-based regulations, increasing the capacity of officials, and community involvement in monitoring forest management is needed.